2011
DOI: 10.1128/jvi.00198-11
|View full text |Cite
|
Sign up to set email alerts
|

The Neutralization Breadth of HIV-1 Develops Incrementally over Four Years and Is Associated with CD4 + T Cell Decline and High Viral Load during Acute Infection

Abstract: ؉ T cell decline, viral load, and CD4 ؉ T cell count at 6 months postinfection but not at later time points, suggesting that early events set the stage for the development of breadth. However, in a multivariate analysis, CD4 decline was the major driver of this association, as viral load was not an independent predictor of breadth. Mapping of the epitopes targeted by cross-neutralizing antibodies revealed that in one individual these antibodies recognized the membrane-proximal external region (MPER), while in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
534
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(571 citation statements)
references
References 59 publications
30
534
6
1
Order By: Relevance
“…Our epitope-mapping studies indicate that the plasma bNAbs bind to an epitope critically dependent on the gp120 N332 glycan, perhaps overlapping that of 2G12 and/or the recently described PGT antibodies. Importantly, broad and potent serum-neutralizing activity in a significant proportion of HIV-1-infected donors has been mapped to N332A-sensitive epitopes (13,14), and broad and highly potent monoclonal antibodies have recently been isolated from such donors (19). Given the rapid generation of bNAbs in this macaque, and the prevalence of bNAbs against N332A-sensitive epitopes in humans, it will be of interest to determine whether bNAbs against glycan epitopes are more rapidly elicited during natural infection and whether they can be more easily induced by vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our epitope-mapping studies indicate that the plasma bNAbs bind to an epitope critically dependent on the gp120 N332 glycan, perhaps overlapping that of 2G12 and/or the recently described PGT antibodies. Importantly, broad and potent serum-neutralizing activity in a significant proportion of HIV-1-infected donors has been mapped to N332A-sensitive epitopes (13,14), and broad and highly potent monoclonal antibodies have recently been isolated from such donors (19). Given the rapid generation of bNAbs in this macaque, and the prevalence of bNAbs against N332A-sensitive epitopes in humans, it will be of interest to determine whether bNAbs against glycan epitopes are more rapidly elicited during natural infection and whether they can be more easily induced by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the N332 glycan is important for formation of the epitopes recognized by the glycan-specific bNAb 2G12 and the recently described PGT bNAbs (18,19). Furthermore, serum-mapping studies have demonstrated that this glycan is critical for broad and potent serumneutralizing activity in a significant proportion of HIV-1-infected humans (13,14 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 <100 >2700 400 >2700 1800 >2700 <100 >2700 <100…”
Section: Evolution Of Plasma Neutralization Breadth and Potency In Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Breadth of plasma neutralizing activity develops incrementally,48 and evidence suggests that protracted exposure to HIV‐1 Env is required 22, 23, 24, 47, 48, 49, 50. Neutralization breadth is not an all‐or‐nothing phenomenon—in one study, about half of a cohort of 205 chronically infected persons were capable of neutralizing about half of a panel of 219 hard‐to‐neutralize (tier 2) HIV‐1 isolates 45.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…36,37 response during HIV infection. One of the most basic examples that anti-HIV humoral immune responses are susceptible to original antigenic sin was observed following vaccination with HIV-1 SF2 gp120.…”
Section: Repertoire Freeze and Selection Of Bnabs And Other Protectivmentioning
confidence: 99%